Synthesis, antimalarial evaluation, Ç-hematin inhibition, and in silico and in vitro ADMET profiling of 4-aminoquinoline-hydroxypyridinone hybrids - Andayi, Warren Andrew (Department of Chemistry, 2015)
Includes abstract.